TIPICO X: report of the 10th interactive infectious disease workshop on infectious diseases and vaccines - Irene Rivero-Calle; Jose Gómez-Rial; Louis Bont; Bradford D. Gessner; Melvin Kohn; Ron Dagan; Daniel C. Payne; Laia Bruni; Andrew J. Pollard; Adolfo García-Sastre; Denise L. Faustman; Albert Osterhaus; et al. (Taylor & Francis Group, 2021)
TIPICO is an expert meeting and workshop that aims to provide the most recent evidence in the field of infectious diseases and vaccination. The 10th Interactive Infectious Disease TIPICO workshop took place in Santiago de Compostela, Spain, on November 21-22, 2019. Cutting-edge advances in vaccination against respiratory syncytial virus, Streptococcus pneumoniae, rotavirus, human papillomavirus, Neisseria meningitidis, influenza virus, and Salmonella Typhi were discussed. Furthermore, heterologous vaccine effects were updated, including the use of Bacillus Calmette-Guérin (BCG) vaccine as potential treatment for type 1 diabetes. Finally, the workshop also included presentations and discussion on emergent virus and zoonoses, vaccine resilience, building and sustaining confidence in vaccination, approaches to vaccine decision-making, pros and cons of compulsory vaccination, the latest advances in decoding infectious diseases by RNA gene signatures, and the application of big data approaches.